Studies of inorganic nanoparticles as collectors for flotation - Naderizand, Behnam (My University, 2011)
The goal of my work was to synthesize an appropriate inorganic nanoparticle as a collector for flotation of glass beads and also to prepare thin films of nickel sulfide. The first step was preparing a very uniform thin layer of nickel sulfide for model adhesion studies. The method employed was successive ionic layer adsorption and reaction (SILAR). The characterization experiments showed a weak deposited layer of nickel sulfide on glass, which was very uneven at low SILAR deposition cycles and very porous at high SILAR deposition cycles.
In the next step, commercial grades of precipitated calcium carbonate (PCC) and colloidal silica were employed as collectors for the flotation of glass beads. Also, stearic acid treatments were carried out on untreated PCC samples. Despite that the mean particle size of PCC particles were in the nano range, they aggregated in aqueous solution and particle size increased to the micron range. Therefore, deposition of these particles onto glass beads was very low and consequently flotation results were not satisfactory. Also, silica particles aggregated when the pH increased to 9 which is the flotation operating pH. These particles did not show good deposition onto glass beads nor good flotation ability. The reasons could be hydrophilicity and aggregation of colloidal silica.
In another series of experiments, stearic acid treated PCC nanoparticles were synthesized with a carbonation method and characterized with electrophoretic mobility, dynamic light scattering, FTIR and contact angle measurements. The flotation experiments have also been carried out and the results showed high recovery percentage of glass beads.
Moreover, silica nanoparticles have been prepared by the Stober method and modified with aminopropyltriethoxy silane (APTS) and mercaptopropyltrimethoxy silane (MPTS) in solvent and aqueous media with post-modification and co-condensation methods. However, flotation results of glass beads when APTS modified silica nanoparticles were employed as collector were not satisfactory which can again related to their hydrophilic characteristics.
Keywords: Chemical Engineering; Chemical Engineering